Analisis Pola Persebaran Spasial Usaha Mikro Kecil dan Menengah (UMKM) di Kabupaten Sukoharjo - Hani'ah Hani'ah (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2018)
UMKM (Micro, Small and Medium Businesses) are one of the business sectors that can increase a region’s income and could open new jobs, especially in Sukoharjo Regency. The development of UMKM in Sukoharjo Regency has increased from 2013 to 2016. The development direction and the spatial pattern of UMKM can be analyzed spatially using nearest neighbour analysis method. Analysis of the UMKM spatial pattern distribution in this study, only focused in a 2 km radius from the centroid industry of PT. Tyfountex Indonesia, PT. Delta Merlin Dunia Tekstil, and PT. Sri Rejeki Isman Tbk, which are the central industry in Sukoharjo Regency. This study using two methods of calculation nearest neighbour are manual calculation with the T-Scale and automatic calculation with P-Value and Z-Score. The distribution of UMKM in three industrial areas are 1,488 business units, which the industrial area of PT. Tyfontex Indonesia has the highest number of UMKM (1,043), while in the PT. Sri Rejeki Isman Tbk (407) and PT. Delta Merlin Dunia Tekstil are 38 business units. Based on the type of business, there are 1,146 business units with a percentage of 77% including in the type of micro business, while 308 businesses or 20.7% include small businesses and 34 medium businesses or with a percentage of 2.3%. The overall of UMKM spatial pattern distribution both from the results of manual and automatic calculations are clustered spatial pattern in each industrial areas with the distribution around the main road.